Application of quality tools to assist in the control of inventory management and optimize the Loucic company’s internal production processes - Zavarize, Matheus; Carvalho, Flavio Lucio Santos de (Brazilian Journal of Production Engineering, 2022)
The search for organizational excellence is a target for small and large companies, with a view to meeting the customer’s needs. Inventory control involves the continuous improvement of internal processes with the use of quality tools, so that objectives can be achieved. To build this, the ProKnow-C (Knowledge Development Process – Constructivist) methodology was used, which seeks to select articles to carry out a systemic analysis of the selected portfolio, highlighting the articles, authors and journals more focused on the topic under study and with greater relevance academic. The study of methodologies for application in the Loucic company, which is inserted in the textile production segment, was carried out. The case study involves the analysis of the company’s processes, applying the PDCA cycle to understand the stages of its production, as well as applying the ABC classification among the company’s most consumed products, to guide and inform it that among the ten most consumed products, some of them need attention and greater control, so that they do not negatively affect the organization’s production system. Finally, it was understood that the actual situation of the company’s stock can be visually improved, in order to facilitate the search for items by employees to start the production process.